Glycerol oxidation assisted electrocatalytic nitrogen reduction: ammonia and glyceraldehyde co-production on bimetallic RhCu ultrathin nanoflake nanoaggregates. Issue 37 (6th September 2019) - Bai, Juan; Huang, Hao; Li, Fu-Min; Zhao, Yue; Chen, Pei; Jin, Pu-Jun; Li, Shu-Ni; Yao, Hong-Chang; Zeng, Jing-Hui; Chen, Yu
Abstract : An NRR/GOR couple electrolyzer was constructed and required only 1.2 V voltage for electrochemical NH3 production in the presence of glycerol. Abstract : As an alternative pathway for present nitrogen fixation methods, the electrocatalytic nitrogen reduction reaction (NRR) under ambient conditions represents an attractive approach for sustainable and economic development of chemistry and biology. In this work, we synthesize bimetallic RhCu ultrathin nanoflake nanoaggregates (RhCu-BUNNs) with atomic thickness by a facile hydrothermal method. For the NRR, bimetallic RhCu-BUNNs exhibit better electrocatalytic activity than monometallic Rh ultrathin nanoflake nanoaggregates (Rh-UNNs) because the introduction of Cu can effectively weaken the competitive hydrogen evolution reaction (HER), which can achieve a high NH3 yield rate (95.06 μg h −1 mgcat −1 ) at −0.2 V potential. Density functional theory (DFT) calculations suggest that the introduction of Cu can effectively lower the energy demand in the *NN reductive process, resulting in NRR activity enhancement. Meanwhile, RhCu-BUNNs also show excellent electrocatalytic activity and selectivity for the glycerol oxidation reaction (GOR). For the electrochemical NH3 production, the sluggish anodic oxygen evolution reaction (OER) increases the overall electrolysis voltage. Herein, we replace the anodic OER with the GOR to assist the NRR using a bifunctional RhCu-BUNN electrocatalyst. Specifically, only 1.2 V whole voltage is required for electrochemical NH3 production in the presence of glycerol, accompanied by the generation of valuable glyceraldehyde at the anode. This work may provide a promising pathway to obtain both NH3 and valuable organic chemicals with high efficiency and low cost.